Application of Assertive Training for the Ability to Control Anger in Patients with Violent Behavior - Suhanda Suhanda; Andan Firmansyah; Hani Monika (Jurnal Vocational Nursing Sciences (VNUS), 2023)
Objective: To be able to provide comprehensive nursing care to patients with violent behavior by applying assertive training techniques. Method: This research method used a qualitative descriptive design with a nursing care process approach including assessment, diagnosis, planning, implementation, and evaluation, which was carried out for 3 days in the Tanjung Room BLUD of the Banjar City Hospital. Enforcement of nursing diagnoses and nursing interventions refers to the IDHS, SIKI, and SLKI, and nursing evaluations are documented using the SOAPIER method. Researchers intervened in the application of assertive exercises with the study population being patients with violent behavior, with the inclusion criteria of patients with a diagnosis of violent behavior and cooperative patients. Accidental sampling technique: this study used one patient with violent behavior. The analysis technique uses interview transcripts and triangulation. Result: The results of this case study show that after being given assertive training technical interventions for 3 days with a duration of 10–20 minutes a day, the problem of nursing violent behavior towards patients was resolved, marked by the patient being able to control anger verbally. assertive training, assertive training therapy, which generally makes the client comfortable, seen from the client's side, is also cooperative and prefers to socialize and talk to other people around him. Conclusion: After nursing care was carried out at the BLUD of the Banjar City Hospital for Ms. S in the Tanjung room with a medical diagnosis of paranoid schizophrenia from March 29 to March 31, 2023, the authors concluded that assertive training is proven to be able to control the anger of patients who experience violent behavior. The benefits will be maximized if done regularly and gradually. So that nurses can carry out these non-pharmacological interventions to control anger in patients with mental disorders with violent behavior problems.